Sinaps-opsporing tussen self en ander in Antjie Krog se Mede-wete (2014) - Visagie, Andries (Tydskrif vir letterkunde, 2019)
The poetry volume Mede-wete by Antjie Krog is a sustained questioning of ethical relations between self and other, an on-goingpreoccupation of Krog in both her poetry and literary non-fiction works. This review article of Mede-wete (also available as Synapse in translation from Afrikaans into English by Karen Press) traces four forms of interconnectedness or synapses that shed light on Krog’s project to establish ethical connections between the self, on the one hand, and, on the other hand, both the human and non-human other. Love and family bonds, reaching out to the cultural other, a sense of shared materiality with the environment, and, consequently, a longing for mystical unity constitute four of the synapses as announced in the title of the volume of poetry. The strength of the often challenging poetry emanates strongly from the daring use of language that includes syllable disturbances and surprising compounds. In many respects, Krog’s impressive volume belies her apparent pessimism that Afrikaans poets and writers today are little more than “thighshifters-in-flinching-language” (Synapse 113).